Credit Risk and Commercial Banks' Performance in Vietnam - Lan, Tianjing (2014)
Commercial banks may suffer losses caused by risk. For modern commercial banks, the potential risk is likely to bring economic losses or reducing the banks’ profitability. Contemporaries, credit risk has become the most significant problem banks facing and is a fatal threat for the healthy operation of commercial banks. Hence, bank credit risk management has got important academic value and practical significance. Vietnam’s economic reform and opening up especially from 2007 to the WTO entry leads to gradual expansion of commercial banks and credit business is also increasing as well, which brings profit to commercial banks together with tons of potential risks. Therefore, gradually improving the credit risk management system becomes the primary task to Vietnam’s banking industry. The aim of this study is identifying the real situation of credit risk in the Vietnamese banking system. This study discussed does not only in detail the definition, category characteristics and management of credit risk from the qualitative aspects, but also from the perspective of quantitative analysis to analyse credit risk quantification. This research summarizes the international studies about credit risk management. Firstly, it refers to the theory of credit risk management and measurement approaches, such as the C-VaR, credit risk strategies and policies, lending guidelines and Basel. Then, combining with the current situation of Vietnamese banks, this thesis analyses the influence of credit risk for the performance of Vietnam’s banks examined by Return on Assets through Panel Regression Model. Finally, this thesis puts forward a proposal for optimizing the issues faced by Vietnamese commercial banks. Consequently, Vietnam cannot do an efficient management on credit risk in its banking sector, especially the biggest credit risk issue, the NPLs problems, facing Vietnam banking industry severely. It indicates that there is still a long way for the Vietnamese banking system to enhance the capability of credit risk management itself.